2018
DOI: 10.1371/journal.pone.0202346
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of vitamin D associated genes in the aorta of coronary artery disease patients with and without rheumatoid arthritis

Abstract: BackgroundVitamin D has an important role in the immune system, and has been linked to rheumatoid arthritis (RA) and coronary artery disease (CAD). The exact mechanisms by which vitamin D is involved in these processes are still unclear. Therefore, we wanted to search for differences in expression of genes involved in the vitamin D receptor (VDR) activation pathway and genes that are known to alter upon vitamin D stimulation, in the aortic adventitia of CAD patients with and without RA.MethodsAffymetrix microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Additionally, the vitamin D associated gene expression within aortic tissue might be influenced in patients with rheumatoid arthritis. Paraoxonases 2, which had antioxidative properties during atherosclerotic processes, was regulated by vitamin D. The expression was lessened during the inflammation [139]. Vitamin D was associated with lessening the inflammatory cytokine.…”
Section: The Role Of Vitamin D and Mscs/pericytes In Vascular Calcifimentioning
confidence: 95%
“…Additionally, the vitamin D associated gene expression within aortic tissue might be influenced in patients with rheumatoid arthritis. Paraoxonases 2, which had antioxidative properties during atherosclerotic processes, was regulated by vitamin D. The expression was lessened during the inflammation [139]. Vitamin D was associated with lessening the inflammatory cytokine.…”
Section: The Role Of Vitamin D and Mscs/pericytes In Vascular Calcifimentioning
confidence: 95%
“…Although Gadd45a gene expression was not modified in peripheral blood mononuclear cells of these RA patients, 20 another study has reported a higher expression of Gadd45a in the adventitia of the ascending aorta of patients with RA compared to non-RA patients (Table 1). 161 In patients with psoriasis, Gadd45a is expressed at higher levels in peripheral and in dermal infiltrating T cells, although no differences are found regarding p38 MAPK activity. 157 The same authors reported that the GADD45A target Uchl1 (ubiquitin carboxyl terminal esterase L1) was hypermethylated at its promoter in psoriatic skin, and that…”
Section: Immunomodulatory Effects Of Gadd45amentioning
confidence: 98%
“…Although Gadd45a gene expression was not modified in peripheral blood mononuclear cells of these RA patients, 20 another study has reported a higher expression of Gadd45a in the adventitia of the ascending aorta of patients with RA compared to non‐RA patients (Table 1). 161 …”
Section: Gadd45a Effects Beyond Cancermentioning
confidence: 99%
“…Studies shows that the primary activation step after 1α,25(OH) 2 D 3 -VDR complex is the transient opening or closing of the chromatin at specific enhancer and TSS with RNA polymerase II and other nuclear adaptor proteins, which determines the regulation (activation or suppression) of primary vitamin D target genes [145] (Figure 4). Nuclear Receptor Corepressor 1 (NCOR1) is a co-repressor that contains nuclear receptor interacting domains and interacts with various nuclear receptors, including VDR [146]. NCOR1 recruits histone deacetylase enzymes (HDACs) which deacetylase histone-tails and thereby condense the DNA structure and prevent gene-transcription.…”
Section: Vitamin D and The Epigenomementioning
confidence: 99%